The Relevance of Bibliometric Analysis to Discover the Area’s Research Efforts: Root Exploit Evolution - Che Akmal Che Yahaya; Ahmad Firdaus; Ferda Ernawan; Wan Isni Sofiah Wan Din (Society of Visual Informatics, 2022)
Malware steals, encrypts, and damages data of the targeted machines for private, money, or fame purposes. The types of malware are root exploit, cryptojacking, Trojan, worms, viruses, spyware, ransomware, and adware. Among these types, root exploit is one of the most destructive malware types since it disguises and obscures all types of malware and provides a mechanism for other malware to carry out malicious acts invisibly. In the interest to review the progress of root exploit efforts globally, there is a need to inspect all publications that involve root exploit. Among all malware reviews previously, to date, there is still no trace of any bibliometric analysis that demonstrates the research impacts of root exploit and trends in bibliometric analysis. Hence, this paper adopts bibliometric analysis specifically on root exploit studies which evaluate: (1) Wordcloud; (2) WordTreeMap; (3) Three fields plot; (4) Thematic evolution; (5) Thematic maps; (6) Correspondence analysis (CA); (7) Dendrogram; and (8) Multiple correspondence analysis (MCA). To conclude, our bibliometric discovers that; 1) Linux and Android become main interest in root exploit studies. 2) Types of root exploit in virtualization layer and studies to detect on this area are increasing. 3) USA and China have become the leaders in root exploit research. 4) Research studies are more towards memory forensics to detect root exploit, which is more promising. 5) Instead of researching new methods of root exploit in compromising victims, root exploit researchers were more focused on detecting root exploits.